Specifics of mental disorders of patients with metabolic syndrome - K. I. Kleban (Kazimierz Wielki University, 2017)
In the general-somatic network there is a steady increase in the number of patients with psychosomatic disorders. Problems of providing adequate psychiatric and psychotherapeutic assistance to this category of patients are related to the motivation of patients to participate in psychological measures and the readiness of the medical system to provide comprehensive care on the basis of the biopsychosocial approach. Mental factors are involved both in the occurrence and course of a metabolic syndrome in the form of a patient's lifestyle and behavior patterns of healthy functioning, and is a consequence of somatic pathology. Mental factors are involved both in the occurrence and course of a metabolic syndrome in the form of a patient's lifestyle and behavior patterns of healthy functioning, and is a consequence of somatic pathology. So mental disorders of metabolic syndrome are manifested in the form of psychosocial maladaptation, neurotic, affective, personality, and organic disorders. Desynchronosis which is a factor of the development of a metabolic syndrome and characterizes the complex chronobiological component of the regulation of psychophysiological functions in norm and under the influence of stress, deserves special attention. Addressing the diagnosis of mental disorders associated with metabolic syndrome is precisely aimed at determining chronobiological disorders of psychosomatic integrated areas and is supposed to improve diagnostic and treatment process and to shorten the treatment of these disorders.